Water Management through the Adoption of Tarpaulin Ponds to Enhance the Self-Sufficiency of the Wanagiri Village Community - Darmadi, Ni Made; Zamri, Sharil Fadli Mohamad; Sadguna, Dewa Nyoman; Kawan, I Made; Suryani, S.A.M.; Arya, I Wayan; Gede, Dewa; Adi, Semara (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Community Service activities are carried out in Wanagiri Village, Sukasada, Buleleng which has abundant water sources but has not been utilized optimally, especially for the Fisheries sector. Fish Group activities are weakening due to lack of motivation and the location for Fisheries Activities is very difficult to reach. The purpose of this community service is to provide solutions to the Merta Lestari Fish Group (Partners) to actively re-cultivate tilapia with the Biofloc system, providing Training on Tarpaulin Pond Making. The method used is by means of Interview, Counseling, Face-to-face, and Direct Practice. With this method, it is hoped that Partners will get knowledge and solutions to the problems faced. Activities are carried out in stages, the First Stage, the Team Provides Counseling, the Second Stage, the Team provides direct practice on making Tarpaulin Pools, conducting evaluations so that Partners really understand, and after that carrying out Coaching. The output targets to be achieved in this activity are publishing the results of activities in international journals, publishing in print/electronic media, making 4-minute activity videos, and obtaining IPR Certificates.